Framing an intervention as focused on one's strength: Does framing enhance therapeutic benefit?. Issue 6 (3rd January 2022) - Murphy, Samuel T.; Cheavens, Jennifer S.; Strunk, Daniel R.
Abstract: Introduction: A capitalization approach to enhancing client skills in cognitive behavioral interventions is focused on enhancing skills that represent relative strengths. This approach may bolster outcomes because the targeted skills are those that clients can most effectively use to recover from negative moods. Alternatively, the benefits might be due to client attitudes about these skills, such as their confidence that they can use these skills effectively. Methods: In an unselected sample of 616 undergraduates, we randomized to one of two brief interventions (a cognitive or mindfulness intervention) and one of two framing conditions (framing the intervention as focusing on a relative strength or a weakness), resulting in four conditions. Participants were then asked to use the skill targeted in their intervention to recover from a sad mood induction. Results: Framing conditions did not differ on expectations of benefit from sustained use of an intervention but did differ on mood recovery. Participants told that the intervention focused on a strength recovered more quickly following the mood induction. There was no difference between the skill interventions. Discussion: Our finding suggests intervention framing positively contributes to the effects of strengths focused treatments, though perhaps not by enhancing treatment expectations.